Språklig och encyklopedisk information i fackordlistor på Internet - Törnqvist, Lars (LexicoNordica, 2007)
In recent years, a great number of dictionaries have been published free of charge on the Internet, general language dictionaries as well as LSP dictionaries. This paper deals with LSP dictionaries published by authorities, associations, companies and single persons, containing anything between ten and more than a thousand headwords. The authors are typically technical experts without any linguistic knowledge. These dictionaries are well worth studying for two reasons. Firstly, they give an overview of actual LSP usage not available in other ways; secondly, they give a general image of the non-lexicographers’ views on dictionaries. Typologically, the dictionaries are extremely heterogenous, but they can be sorted into two main categories: simple glossaries and explaining dictionaries. The simple glossaries contain equivalents in two or more languages without any comments on grammar or meaning. Most of them are made for one special type of text, e.g. source documents for genealogists. The explaining dictionaries are in most cases included in larger websites, explaining the the terminology used in other pages of the same site. The aim of these dictionaries is to give the customers or clients knowledge on the terminology in order to facilitate communication, e.g. in ordering envelopes from a printer or asking for subsidies from a government authority. The definitions in these dictionaries often seamlessly turn into encyclopaedic articles. Explicit information on linguistic properties such as part of speech, flexion or pronunciation is hardly ever present in any Internet LSP dictionary.